2023
DOI: 10.1039/d2na00530a
|View full text |Cite
|
Sign up to set email alerts
|

Functional nano-systems for transdermal drug delivery and skin therapy

Abstract: Functional nano-systems have been applied as a promising strategy for transdermal drug delivery and skin therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(30 citation statements)
references
References 243 publications
0
30
0
Order By: Relevance
“…They also showed how the surface charge can affect functional nano-system permeation and penetration on the skin. 87 In a study done by testing Artemether (ART) loaded nanogels on pig ear skin, the nanogels showed reasonable drug concentration in the living epidermis even though higher in the stratum corneum. ART-nanogels had good pH storage stability, viscosity, spread ability, drug content, in vitro drug release, skin tolerance, and occlusivity leaving a thin film after application on the skin due to good hydration and ability to prevent skin trans-epidermal water loss.…”
Section: Polymers In Nanogel Formulation For Topical Treatmentmentioning
confidence: 99%
“…They also showed how the surface charge can affect functional nano-system permeation and penetration on the skin. 87 In a study done by testing Artemether (ART) loaded nanogels on pig ear skin, the nanogels showed reasonable drug concentration in the living epidermis even though higher in the stratum corneum. ART-nanogels had good pH storage stability, viscosity, spread ability, drug content, in vitro drug release, skin tolerance, and occlusivity leaving a thin film after application on the skin due to good hydration and ability to prevent skin trans-epidermal water loss.…”
Section: Polymers In Nanogel Formulation For Topical Treatmentmentioning
confidence: 99%
“…51 The skin penetration mechanism used by liposomes is unclear, but there are several possibilities: (i) liposomes remain on the surface of the skin and then break, allowing nutrients to diffuse freely into the skin; (ii) liposomes can fuse with skin lipids, leading to early release of nutrients from the liposomes before reaching deeper skin layers and (iii) intact liposomes permeate and enter the skin (Figure 5). 7,51 Liposome occlusion may improve skin hydration and allow penetration by disruption of skin lipid structures for the penetration of nutrients into different skin layers. 52 Liposomes have been used to deliver various nutrients, such as vitamins.…”
Section: Liposomesmentioning
confidence: 99%
“…Compared to conventional administration strategies such as oral administration or intravenous injection, transdermal delivery utilizes painless self‐administration at home, outside a hospital setting. These delivery systems also can avoid first‐pass metabolism and significantly increase the bioavailability of therapeutic drugs, improving drug stability and biodistribution and allowing sustained release 7,8 . The application and development of transdermal delivery systems represent an opportunity to allow great use of many nutrients with promising human health benefits, supporting the need to take more account of specific nutritional needs in specific states.…”
Section: Introductionmentioning
confidence: 99%
“…4−6 The use of nanocarriers is considered a promising method to enhance transdermal drug delivery efficiency without causing tissue damage. 1,7 By encapsulating drug molecules within a nanostructure, it is possible to mitigate the limited solubility of hydrophobic molecules, protect them from enzymatic degradation, and minimize the exposure of healthy tissues to toxic compounds. 8−12 To further enhance the skin permeation efficiency of nanocarriers, in previous studies, they have been decorated with penetration-enhancing agents (PEAs), including small molecules, peptides, and aptamers.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Transdermal drug delivery offers various advantages over oral and intravenous modalities, such as the avoidance of first-pass metabolism, easy accessibility, improved patient compliance, and reduced systemic-derived side effects. As the skin is a complicated barrier and difficult to overcome, various strategies have been devised to effectively deliver drug molecules transdermally (e.g., nanoneedle, thermal ablation, electroporation, iontophoresis, and sonophoresis). The use of nanocarriers is considered a promising method to enhance transdermal drug delivery efficiency without causing tissue damage. , By encapsulating drug molecules within a nanostructure, it is possible to mitigate the limited solubility of hydrophobic molecules, protect them from enzymatic degradation, and minimize the exposure of healthy tissues to toxic compounds. …”
Section: Introductionmentioning
confidence: 99%